Model Ambiguity versus Model Misspecification in Dynamic Portfolio Choice - MAENHOUT, PASCAL J.; XING, HAO; BALTER, ANNE G. (Journal of Finance, 2026)
ABSTRACT We study aversion to model ambiguity and misspecification in dynamic portfolio choice. Risk‐averse investors (relative risk aversion ) fear return persistence, while risk‐tolerant investors () fear mean reversion, when confronting model misspecification concerns of identically and independently distributed (IID) returns. The intuition is that risk‐averse investors, who want to hedge intertemporally, endogenously fear return persistence, which precludes hedging. A log investor is myopic and unaffected by model misspecification, therefore only worrying about model ambiguity. Our model can generate belief scarring, nonparticipation in equity markets, and extrapolative return expectations. Extending beyond IID returns, we study model misspecification for a mean‐reverting Sharpe ratio.